Trend in the Learning Model of Islamic Education Over a Decade: A Bibliometric Review - Novia Rizqiatul Umami; Akhmad Affandi; Ahmad Arifuddin; Muhammad Jauhari Sofi (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2025)
This research aims to analyze publication trends related to learning models in Islamic Religious Education over the past decade using bibliometric analysis. The analysis was conducted using Scopus, Excel, and the VOSviewer application. The study covers the period from 2014 to 2024, identifying a total of 233 relevant articles. The results indicate a significant increase in publications on learning models each year, with 2022 having the highest number. Indonesia remains the most active country in publishing research on this topic until 2024. The three leading journals in this field are Jurnal Pendidikan Islam, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung; Jurnal Pendidikan Agama Islam, Department of Islamic Religious Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Kalijaga Yogyakarta; and Multidisciplinary Digital Publishing Institute (MDPI) in third place. The most productive affiliations are Universitas Pendidikan Indonesia and UIN Sunan Gunung Djati Bandung. In addition, five authors, i.e. Kistoro, H.C.A; Rahmat, M; Supriyadi; Syafii; and Tambak, S, have each published at least three articles on the topic. These findings imply that research on learning models in Islamic Religious Education is expected to remain popular in the coming decades.Keywords: Learning Models, Islamic Religious Education, Bibliometric Analysis.